(untitled) (Jurnal Kemanusiaan, 2017)
This article aims to examine the extent of compliance among users of the Islamic banking institutions (IBI), specifically Muslim individuals, towards the selection of the bank according to the Muslim ideal (PPBMMI). Does an ideal Muslim society exists, especially in Terengganu, the earliest state where received the advent of Islam in Malaysia and famous in implementing administrative system based on Islam? This article tries to answer this question focusing on the discussion of the analysis of the relationship between the PPBMMI and the behaviour selection of IBIS among Muslims. Pearson correlation test performed on 429 Muslim users in Terengganu showed a positive relationship between the behaviour selection of IBIS with PPBMMI. However, the strength of the relationship between the two variables is only moderate. Artikel ini bertujuan meneliti sejauh mana patuhnya pengguna institusi perbankan Islam (IPI), khususnya individu Muslim terhadap penentu pemilihan bank menurut Muslim ideal (PPBMMI). Apakah wujud masyarakat Muslim yang ideal, khususnya di Terengganu, negeri terawal menerima kedatangan Islam di Malaysia dan cukup terkenal dalam melaksanakan sistem pentadbiran berteraskan Islam? Artikel ini cuba menjawab persoalan ini dengan menumpukan perbincangan kepada dapatan analisis hubungan antara PPBMMI dengan gelagat pemilihan IPI dalam kalangan Muslim. Ujian korelasi pearson yang dilakukan ke atas 429 orang pengguna Muslim di Terengganu menunjukkan hubungan yang positif antara gelagat pemilihan IPI dengan PPBMMI. Walau bagaimanapu